Genome‐Wide Mapping of 5′ Isoforms with 5′‐Seq. Issue 4 (21st April 2023) - Gvozdenov, Zlata
Abstract: The transcriptome is far more complex than previously assumed. Transcripts from the same gene can differ in terms of transcription start site, transcription end site, or pattern of splicing, and growing evidence supports the functional importance of these distinct transcript isoforms. Easily identifying these isoforms experimentally via library construction and high‐throughput sequencing is crucial. Current library construction methods for identifying transcription start sites (5′ transcript isoforms) involve large number of steps and (expensive) reagents, utilization of cDNA intermediates for adapter ligation, and are less suitable for studying low‐abundance isoforms. Here, I describe a quick protocol for the generation of sequencing libraries to define capped 5′ isoforms (5′‐Seq) of various abundances in yeast and suggest a 5′ isoform data analysis pipeline. The protocol relies on the utilization of a dephosphorylation‐decapping method (oligo‐capping) to generate a sequencing library from mRNA fragments and is a simplification of previously published 5′ isoform protocols in terms of the handling steps, time, and cost. This method is exemplified using Saccharomyces cerevisiae mRNA, but it can be applied to various cellular conditions to study the effects of 5′ transcript isoforms on transcriptional and/or translational regulation. © 2023 Wiley Periodicals LLC. Basic Protocol : Construction of a DNA sequencing library from capped 5′ isoforms Support Protocol : Sequencing data analysis